Remarkable anoxia tolerance by stoneflies from a floodplain aquifer - Rachel L. Malison; Bonnie K. Ellis; Amanda G. DelVecchia; Hailey Jacobson; Brian K. Hand; Gordon Luikart; H. Arthur Woods; Maribet Gamboa; Kozo Watanabe; Jack A. Stanford (Ecology, 2020)
Alluvial aquifers are key components of river floodplains and biodiversity worldwide, but they contain extreme environmental conditions and have limited sources of carbon for sustaining food webs. Despite this, they support abundant populations of aquifer stoneflies that have large proportions of their biomass carbon derived from methane. Methane is typically produced in freshwater ecosystems in anoxic conditions, while stoneflies (Order: Plecoptera) are thought to require highly oxygenated water. The potential importance of methane‐derived food resources raises the possibility that stonefly consumers have evolved anoxia‐resistant behaviors and physiologies. Here we tested the anoxic and hypoxic responses of 2,445 stonefly individuals in three aquifer species and nine benthic species. We conducted experimental trials in which we reduced oxygen levels, documented locomotor activity, and measured survival rates. Compared to surface‐dwelling benthic relatives, stoneflies from the alluvial aquifer on the Flathead River (Montana) performed better in hypoxic and anoxic conditions. Aquifer species sustained the ability to walk after 4–76 h of anoxia vs. 1 h for benthic species and survived on average three times longer than their benthic counterparts. Aquifer stoneflies also sustained aerobic respiration down to much lower levels of ambient oxygen. We show that aquifer taxa have gene sequences for hemocyanin, an oxygen transport respiratory protein, representing a possible mechanism for surviving low oxygen. This remarkable ability to perform well in low‐oxygen conditions is unique within the entire order of stoneflies (Plecoptera) and uncommon in other freshwater invertebrates. These results show that aquifer stoneflies can exploit rich carbon resources available in anoxic zones, which may explain their extraordinarily high abundance in gravel‐bed floodplain aquifers. These stoneflies are part of a novel food web contributing biodiversity to river floodplains.